2016
DOI: 10.3748/wjg.v22.i21.4977
|View full text |Cite
|
Sign up to set email alerts
|

Current status of laparoscopic and robotic ventral mesh rectopexy for external and internal rectal prolapse

Abstract: External and internal rectal prolapse with their affiliated rectocele and enterocele, are associated with debilitating symptoms such as obstructed defecation, pelvic pain and faecal incontinence. Since perineal procedures are associated with a higher recurrence rate, an abdominal approach is commonly preferred. Despite the description of greater than three hundred different procedures, thus far no clear superiority of one surgical technique has been demonstrated. Ventral mesh rectopexy (VMR) is a relatively ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 79 publications
4
66
2
4
Order By: Relevance
“…The patients undergoing VMR in this study demonstrated a significant improvement in defaecation with 76% experiencing improvement in ODS symptoms. This falls into the 55-86% range cited by van Iersel et al [10].…”
Section: Discussionmentioning
confidence: 50%
“…The patients undergoing VMR in this study demonstrated a significant improvement in defaecation with 76% experiencing improvement in ODS symptoms. This falls into the 55-86% range cited by van Iersel et al [10].…”
Section: Discussionmentioning
confidence: 50%
“…Although diagnostic criteria have existed for some time for functional gastrointestinal disorders, establishing the correct diagnosis and identifying aetio‐pathogenesis of CC are key first steps required to optimise the clinical outcome for the patient. As new research has provided a better understanding of the range of primary and secondary causes of CC, so it has also identified new targets for physical and pharmacological treatment of the disease . With new behavioural, pharmacological and surgical treatments becoming available it is essential to recognise when a treatment is failing to work adequately and thus should be switched.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the outcomes from medical practice, the use of surgical meshes for the management of both SUI and POP is accompanied by benefits but also risks (Barber, ), which in some cases can lead to serious life‐threating conditions, as will be discussed in the following paragraphs (Falagas, Velakoulis, Iavazzo, & Athanasiou, ; Keys, Campeau, & Badlani, ; van Iersel et al, ; Wu, ).…”
Section: The Advent Of Surgical Meshes In Pop Surgerymentioning
confidence: 99%